Rekonstruksi Citra Pekerja Migran Indonesia Studi Personal Branding TKI Sebagai Content Creator Tiktok dan Implikasinya pada Persepsi Publik - Aiynun Zariah; Zulaikha Zulaikha; Nur’Annafi Firna Syam Maella (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2026)
Indonesian Migrant Workers (PMI) face the problem of stigmatization and negative image that has been rooted in public perception for several decades, where the social construction of TKI is dominated by narratives of exploitation, violence, and victimization reinforced by conventional mass media coverage. The phenomenon of TKI emerging as content creators on the TikTok platform opens new opportunities for migrant workers to represent themselves independently and build personal Branding that has the potential to reconstruct their image in public perception. This study aims to analyze the personal Branding strategies of TKI content creators on TikTok, measure the engagement patterns and reach of the content produced, and evaluate the transformation of public perception toward Indonesian migrant workers as an implication of these digital communication practices. This study uses a qualitative approach with a case study design to explore the process of image reconstruction through personal Branding on the TikTok platform. Data were collected through in-depth interviews with five TKI content creators who have followers ranging from 750 thousand to 2.3 million, interviews with 50 active followers, and interviews with two digital communication experts. The research findings show that TKI content creators implement personal Branding strategies through content authenticity, narrative consistency, and positioning differentiation with engagement rates. Public perception changed significantly with a decrease in negative perception from 68 percent to 18 percent and an increase in positive perception from 10 percent to 55 percent within an exposure period of more than 12 months. Image reconstruction occurs through three mechanisms: humanization that displays the human side of TKI, normalization that elevates the profession as work worthy of respect, and inspiration that demonstrates their positive achievements. This study recommends that the government and related stakeholders support digital literacy for migrant workers to optimize social media platforms as a means of empowerment, as well as promote policies that protect and appreciate the contribution of TKI as an integral part of national economic development.